THE STUDENT MANAGEMENT IN IMPROVING NON-ACADEMIC ACHIEVEMENT AT AL HIKMAH ANJATAN INDRAMAYU ISLAMIC JUNIOR HIGH SCHOOL - Dulkalim, Dulkalim (Pergunu Jawa Barat, 2025)
This study aims to describe and analyze the role of student affairs management in enhancing non-academic achievement at SMP IT Al Hikmah Anjatan Indramayu. The main focus of this research is on the implementation of talent and interest development programs, student empowerment strategies, and the forms of intrinsic motivational support applied by the school. The objectives of this study include: 1) Analyzing and predicting student affairs management in improving students’ non-academic achievement at SMP IT Al Hikmah Anjatan Indramayu; 2) Analyzing and predicting the supporting and inhibiting factors in improving students’ non-academic achievement at the same institution; and 3) Analyzing and predicting the outcomes of improved non-academic achievement through student affairs management at SMP IT Al Hikmah Anjatan Indramayu. This research employs a qualitative approach with a case study method. Data collection techniques include in-depth interviews, participatory observation, and documentation. The results of this study show that structured and character-based student affairs management at SMP IT Al Hikmah Anjatan Indramayu has proven effective in enhancing students' non-academic achievements. This is reflected in the success of various extracurricular activities that actively involve students and foster responsibility, discipline, and teamwork. Additionally, intrinsic motivation and an inclusive school culture greatly impact students' enthusiasm in participating in non-academic activities. Student empowerment through involvement in decision-making and active teacher guidance fosters greater independence and accountability among students regarding both the process and outcomes of their activities. Furthermore, the development of students’ talents and interests through activities tailored to their individual potentials boosts engagement and achievement. The school provides space and support for students to express their interests whether in arts, sports, or religious activities which significantly contributes to building self-confidence and leadership skills.